Lulu's song - Wallace, Karen; Williams, Lisa (Wayland London, 2009)
Start Reading is a new series of highly enjoyable books for beginning readers at KS1. Down in the Jungle is at Orange Band 6 of the Start Reading programme. Follow the adventures of Flora the elephant, Lulu the parrot, Spot the leopard and Monty the monkey